Pneumococcal nasopharyngeal carriage in pre-school children, parents, and community- dwelling older adults during the introduction of the 13 valent pneumococcal conjugate vaccine. (24th May 2012) - Hamaluba, M; Lazarus, R; John, TM; Zafar, A; Brueggemann, AB; Crook, D; Snape, MD; Pollard, AJ
Abstract : Background and aims: In the UK, a seven valent pneumococcal conjugate vaccine (PCV7) was introduced in 2006 for children under 2 years of age in a 3 dose schedule; 2, 4, 12 months of age and was found to be highly effective against vaccine-types, but serotype replacement reduced the overall impact against pneumococcal disease. In April 2010 PCV13 replaced PCV7 in the routine infant schedule without a catch-up campaign. We assessed the prevalence and serotype distribution of pneumococcal nasopharyngeal carriage in 3 generations prior to widespread use of PCV13. Methods: Children who received 3 doses of PCV7 (age range 21– 55 months), their parents and a cohort of community-dwelling adults aged 65 and over were recruited. A swab was taken, placed in STGG media and cultured within 8 hours. Pneumococci were cultured, serotyped using the Quellung reaction and genotyped using multilocus sequence typing. Results: S.pneumoniae was recovered from 46% (270/592) of children, 12% (12/100) of parents and 6.2% (37/600) of older adults. PCV13 vaccine-types were found in 20% of children (56/270).The 10 most common serotypes among children, in descending order, were: 19A, 11A, 23B, 6C, nontypeables, 3, 22F, 23A, 35F and 21. 4/12 serotypes in parents and 3/37 in older adults were vaccine-types. Conclusions: 18 months after the launch of PCV13 in the UK, vaccine-type pneumococci were still circulating among preschool children although most isolates were non-vaccine types. Carriage rates in parents and older adults were lower. Further studies will allow monitoring of the impact of the vaccine once PCV13 immunity is fully established in early childhood.